Pemanfaatan Energi Putaran Roda Sepeda Motor untuk Menghasilkan Energi Listrik - Jhon Malta; Fuadi Mustafa (METAL: Jurnal Sistem Mekanik dan Termal, 2020)
This research is conducted to convert the rotating energy of the wheel of a motorcycle as an alternative electricity power plant. The rotating wheel contacts a roller and then transmitted by belt to the generator. The generator generates the electric current and then converted using an inverter to produce alternating current (AC) with the voltage 220 volts. A battery is used to stabilize the output voltage. Based on the reference, the needed energy for the cell to charge is 13.0 volts to 13.9 volts. This tool can produce this voltage with 170 – 180 rpm of the wheel rotation, which is obtained in the gear 2 of the motorcycle Honda Supra X 125R.